MODERN METHODS OF ASSESSING THE QUALITY OF VOCATIONAL EDUCATION AND TRAINING IN THE EUROPEAN UNION COUNTRIES (Innovative professional education, 2025)
Based on the analysis of scientific and information sources, some modern methods of assessing the quality of vocational education and training in the countries of the European Union are explained. Some features of the European model of quality assurance of vocational education and training, as well as criteria and methods for assessment, are characterized
Keywords: method, assessment, quality, vocational education, training, European Union